Relationship between corporate identity elements and corporate image in Malaysian government-linked companies - Muhami, Aida (2018)
Corporate identity as a management strategy has derived from the simple visual representation of an organisation to a more complex corporate strategy over the past thirty years. There is now considerable research to suggest that effective corporate identity management results in creating a positive image and simultaneously helps organisational members to align their work with the organisation’s vision and , at the same time there are many factors that contributing in the decision making solely based on the corporate identity being implemented in the organization. For that reason, the objective of this study is to identify the application of the seven elements at several Government Linked Companies (GLCs) in Malaysia in terms of executive officers and their relationship to corporate image. There are seven elements of corporate identity management which is based on Melewar and Karaosmanoglu (2006) are divided into namely corporate structure, corporate strategy, corporate culture, corporate communication, corporate behaviour, corporate design and industry identity. A total of 400 staff were involved as respondents in this descriptive study. Questionnaires were used to carry out this survey based on voluntary sampling method. The collected data was analysed using Descriptive Statistics and Multiple Regression Test. Based on the findings of this study, it is found that the descriptive analysis result for all of corporate identity elements and corporate image are at the average level. The Multiple Regression Test shows that out of the seven elements of Corporate Identity Management, only Management of Corporate Behaviour and Management of Industry Identity that contribute to the changes in the Organisational Corporate Image of the Government Linked Companies (GLCs). The result of this research suggests that both the elements mentioned earlier are given attention in order to improve the image of an organisation.